UAV-Based Bistatic SAR-Imaging Using a Stationary Repeater - Alexander Grathwohl; Benedikt Meinecke; Marius Widmann; Julian Kanz; Christian Waldschmidt (IEEE Journal of Microwaves, 2023)
Synthetic aperture radar (SAR) is an established technique for high-resolution radar imaging relying on the ego-motion of the radar. The long coherent integration time of the radar in conjunction with a linear or circular trajectory enables the illumination of targets under different observation angles leading to robustness against short-time interference signals. The use of a bistatic setup to simultaneously acquire multiple observation angles further increases the aforementioned benefits. In this work, a bistatic SAR system using an active repeater is proposed, in the following called Bistatic Repeater-SAR (BR-SAR). In BR-SAR the repeater acts as a second observer providing a bistatic path with low system cost and hardware effort. This article discusses the BR-SAR approach with all signal processing and hardware considerations necessary to build the bistatic radar system. This includes a description of the full system and signal chain with a focus on the signal separation and evaluation of both monostatic and bistatic signals and the subsequent SAR processing. The approach is verified via simulations and measurements, in which conventional SAR is compared to the proposed BR-SAR system. Hardware effects leading to a deteriorated system performance of the bistatic system are analyzed and countermeasures are discussed and implemented. Finally, the benefits of the bistatic system are demonstrated based on a realistic measurement scenario.